Profesionalisme Guru Bimbingan dan Konseling di Masa Pandemi Covid-19 - M. Syakur; Ahmad Andry Budianto (Fakultas Dakwah Universitas Ibrahimy, 2021)
The profession of guidance and counseling teacher or school counselor is substantial because the guidance and counseling teacher serves as a helper and the assistance process is called helping. other helpful professions. Science and technology are the basis for guidance and counseling teachers for the implementation of professional professional services and are maintained by a code of ethics that is specifically formulated for the profession. The method in this study uses the library research method. The results of this study are professional guidance and counseling teachers, namely: able to develop non-test instruments for the purposes of counseling services; can apply non-test instruments to reveal the actual conditions of students related to the environment; can describe the assessment used in guidance and counseling services according to the needs of students; can choose the type of assessment according to the needs of guidance and counseling services; can administer the assessment; can administer assessments to reveal student problems; and can display professional responsibilities in accordance with the principles of guidance and counseling in the practice of assessment